Enhancing OSGi with real‐time Java support. (29th January 2012) - Basanta‐Val, P.; García‐Valls, M.; Estévez‐Ayres, I.
SUMMARY OSGi was designed with embedded systems in mind, its current support is insufficient for coping with one main characteristic of many embedded systems: real‐time performance. This article analyzes different key issues in providing OSGi with real‐time Java performance covering motivational issues, and different integration ways and challenges stemming from the integration. It also contributes a general framework for introducing real‐time performance in OSGi, which is called the real‐time for OSGi framework. The framework uses real‐time Java virtual machines and the real‐time specification for Java. The adoption of this framework allows cyber‐physical systems to experience real‐time Java performance in their applications. The framework introduces several integration levels for OSGi and real‐time specification for Java, and specific real‐time OSGi services. An empirical implementation was carried out using standard software, which was extended with the new defined services. Copyright © 2012 John Wiley & Sons, Ltd.